2018
DOI: 10.21037/cdt.2018.06.09
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet agents in uncertain clinical scenarios—a bleeding nightmare

Abstract: Despite over 40 years since the first percutaneous coronary intervention (PCI) was performed, the optimal dual antiplatelet therapy (DAPT) regime poses a significant challenge for clinicians, especially in certain scenarios. DAPT is the standard of care in PCI following an acute coronary syndrome (ACS) or for elective patients with obstructive coronary artery disease (CAD). There remains significant uncertainty regarding DAPT in patients at high risk of bleeding, such as the elderly and patients requiring anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…It is important to note that the TT is frequently associated with the interruption of DAPT due to the associated increased bleeding events. 22,23 This may lead to an increase in ischemic complications along with ischemia related to anemia resulting from hemorrhagic episodes. With the use of DOACs, that are proven to reduce bleeding complications compared to warfarin in a variety of settings, it is prudent to expect that ischemic complications may be lowered when added to DAPT.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the TT is frequently associated with the interruption of DAPT due to the associated increased bleeding events. 22,23 This may lead to an increase in ischemic complications along with ischemia related to anemia resulting from hemorrhagic episodes. With the use of DOACs, that are proven to reduce bleeding complications compared to warfarin in a variety of settings, it is prudent to expect that ischemic complications may be lowered when added to DAPT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have linked a prothrombotic state with promotion of fibrosis [23,24], and there is strong evidence for avoiding warfarin anticoagulation in patients with IPF [25]. A recent review of antiplatelet therapy found that while bleeding risk was often considered a minor problem, it is associated with an increased risk of mortality and morbidity [26]. Despite this, registry data suggest that anticoagulants/antiplatelet drugs are still prescribed to patients with IPF [27].…”
Section: Discussionmentioning
confidence: 99%
“…For the comparison of baseline characteristics between HPR and non-HPR subgroups among patients with and without with DAPT. 4,5 To aid physicians in identifying patients at high bleeding risk (HBR), the Academic Research Consortium (ARC) published a consensus document in 2019, which provided a consistent definition of HBR to be used in clinical trials and routine practice to evaluate and standardize treatment. 6 Recent investigations confirmed the applicability of ARC-HBR for identifying bleeding risk in routine clinical practice.…”
Section: Methodsmentioning
confidence: 99%